PAI-1 secreted from metastatic ovarian cancer cells triggers the tumor-promoting role of the mesothelium in a feedback loop to accelerate peritoneal dissemination. (1st February 2019) - Peng, Yang; Kajiyama, Hiroaki; Yuan, Hong; Nakamura, Kae; Yoshihara, Masato; Yokoi, Akira; Fujikake, Kayo; Yasui, Hiroaki; Yoshikawa, Nobuhisa; Suzuki, Shiro; Senga, Takeshi; Shibata, Kiyosumi; et al.
Abstract: The mesothelium, covered by a continuous monolayer of mesothelial cells, is the first protective barrier against metastatic ovarian cancer. However, mesothelial cells release tumor-promoting factors that accelerate the process of peritoneal metastasis. We identified cancer-associated mesothelial cells (CAMs) that had tumor-promoting potential. Here, we found that plasminogen activator inhibitor-1 (PAI-1) induced the formation of CAMs, after which CAMs increasingly secreted the oncogenic factors interleukin-8 (IL-8) and C-X-C motif chemokine ligand 5 (CXCL5), further promoting the metastasis of ovarian cancer cells in a feedback loop. After the formation of CAMs, PAI-1 activated the nuclear factor kappa B (NFκB) pathway in the CAMs, thus transcriptionally upregulating the expression of the downstream NFκB targets IL-8 and CXCL5. Moreover, PAI-1 correlated with peritoneal metastasis in ovarian cancer patients and indicated a poor prognosis. In both ex vivo and in vivo models, after PAI-1 expression was knocked down, the metastasis of ovarian cancer cells decreased significantly. Therefore, targeting PAI-1 may provide a potential target for future therapeutics to prevent the formation of CAMs and alleviate peritoneal metastasis in ovarian cancer patients. Highlights: Metastatic ovarian cancer cells actively interact with normal peritoneal mesothelial cells. Plasminogen activator inhibitor-1 is one of the secretory affecting factors. Cancer-associated mesothelial cells are transformed from normal mesothelial cells during the interaction. As a response, cancer-associated mesothelial cells release oncogenic factors to accelerate the peritoneal metastasis. The activation of nuclear factor κB pathway in cancer-associated mesothelial cells accounts for the tumor-promoting effect.